Pengaruh Partisipasi Penganggaran Pada Senjangan Anggaran Dengan Gaya Kepemimpinan Dan Karakter Personal Sebagai Variabel Pemoderasi - Mendi, I Putu Suardi Antara Putra; Suparsto, Herkulanus Bambang (E-Jurnal Akuntansi, 2019)
Every company in carrying out its operations has clear objectives as a guideline in carrying out its duties by each of its employees. This study aims to determine the effect of leadership style and personal character in moderating the relationship between budgetary participation on budgetary slack. The approach used in this study is a quantitative approach in the form of associative causality. The object of research in this study is budgetary slack. The method of determining the sample of respondents in this study using a purposive sampling method. The number of respondents used as the study sample is 80 people. Data collection methods used are by distributing questionnaires. The data analysis technique used is Moderated Regression Analysis (MRA). The results of this study are that budgetary participation has a negative and significant effect on budgetary slack. Leadership style and personal character strengthen the influence of budgetary participation on budgetary slack. Keyword : Budgeting, leadership, personal character.